2014
DOI: 10.5935/0034-7280.20140063
|View full text |Cite
|
Sign up to set email alerts
|

Visual impairment, rehabilitation and International Classification of Functioning, Disability and Health

Abstract: Objective: To describe the characteristics of people with visual impairment who participated in the Visual Rehabilitation Groups, according to the ICD-10 and the International Classification of Functioning, Disability and Health (ICF). Methods: Quantitative, cross-sectional survey, developed in a university rehabilitation research center between october and december 2012. The users from the Visual Rehabilitation Groups were invited; 13 of them agreed to participate. We performed an occupational therapy evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 20 publications
(48 reference statements)
0
11
0
5
Order By: Relevance
“…It is expected a 50% increase in number of individuals affected by AMD until 2020 (7) . There is no official epidemiologic statistic of AMD in Brazil but some studies suggest numbers (8) . In a recent global metaanalysis including 149 studies, only 39 used international protocols of screening and imaging and were considered reliable.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected a 50% increase in number of individuals affected by AMD until 2020 (7) . There is no official epidemiologic statistic of AMD in Brazil but some studies suggest numbers (8) . In a recent global metaanalysis including 149 studies, only 39 used international protocols of screening and imaging and were considered reliable.…”
Section: Introductionmentioning
confidence: 99%
“…(9) Patients diagnosed with Keratoconus reported that due to the symptoms of the disease it was difficultto carry out the daily activities.The visual loss led patients to present functional losses, limiting and restricting the participation and performance in everyday activities, interfering in independence, autonomy and quality of life that they had. (10) This way, participants described they tried to adapt to the difficulties, and tried to wear eye prosthesis, however they did not work as expected.Research describes that incipient cases are controlled with glasses, contact lenses may be used in mild cases, and more severe cases may be treated with deep anterior lamellar keratoplasty and corneal transplant.However, it depends on each individual's adaptation to the use of prosthesis. (2) Other research shows that the use of resources has been proved beneficial to the expansion of functionality, showing the influence of external factors on the performance of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…Por tanto, la rehabilitación visual se puede definir como un proceso que se construye de acuerdo con la identificación constante de las necesidades y demandas de los individuos, que involucra su estado actual de salud, intereses, contexto y expectativas. Las acciones deben incluir la asistencia de un equipo multidisciplinario para proporcionar apoyo oportuno y completo a las personas con discapacidades 11 .…”
Section: Introductionunclassified